Accretion geometry of the neutron star low mass X-ray binary Cyg X-2 from X-ray polarization measurements. Issue 3 (20th December 2022) - Farinelli, R; Fabiani, S; Poutanen, J; Ursini, F; Ferrigno, C; Bianchi, S; Cocchi, M; Capitanio, F; De Rosa, A; Gnarini, A; Kislat, F; Matt, G; et al.
ABSTRACT: We report spectro-polarimetric results of an observational campaign of the bright neutron star low-mass X-ray binary Cyg X-2 simultaneously observed by IXPE, NICER, and INTEGRAL . Consistently with previous results, the broad-band spectrum is characterized by a lower-energy component, attributed to the accretion disc with kT in ≈ 1 keV, plus unsaturated Comptonization in thermal plasma with temperature kT e = 3 keV and optical depth τ ≈ 4, assuming a slab geometry. We measure the polarization degree in the 2–8 keV band P = 1.8 ± 0.3 per cent and polarization angle ϕ = 140° ± 4°, consistent with the previous X-ray polarimetric measurements by OSO-8 as well as with the direction of the radio jet which was earlier observed from the source. While polarization of the disc spectral component is poorly constrained with the IXPE data, the Comptonized emission has a polarization degree P = 4.0 ± 0.7 per cent and a polarization angle aligned with the radio jet. Our results strongly favour a spreading layer at the neutron star surface as the main source of the polarization signal. However, we cannot exclude a significant contribution from reflection off the accretion disc, as indicated by the presence of the iron fluorescence line.